Altered levels of IFN-γ, IL-4, and IL-5 depend on the TLR4 rs4986790 genotype in COPD smokers but not those exposed to biomass-burning smoke - Gutiérrez-Romero, Karla Jazmín; Falfán-Valencia, Ramcés; Ramírez-Venegas, Alejandra; Hernández-Zenteno, Rafael De Jesus; Flores-Trujillo, Fernando; Sansores-Martínez, Raúl; Ramos-Martínez, Espiridión; Pérez-Rubio, Gloria (Frontiers in Immunology, 2024)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is associated with tobacco smoking and biomass-burning smoke exposure. Toll-like receptor 4 (TLR4) single nucleotide polymorphisms (SNPs) may contribute to its pathogenesis. The study aimed to assess the association of rs4986790 and rs4986791 in the TLR4 gene in a Mexican mestizo population with COPD secondary to tobacco smoking (COPD-TS) and biomass-burning smoke (COPD-BBS) and to evaluate whether the genotypes of risk affect cytokine serum levels. Materials and methods: We enrolled 2,092 participants and divided them into two comparisons according to their environmental exposure. SNPs were genotyped using TaqMan probes. Serum cytokine levels (IL-4, IL-5, IL-6, IL-10 and INF-γ) were quantified by ELISA. Results: The rs4986790 AA genotype in COPD-TS was associated with a higher COPD risk (OR=3.53). Haplotype analysis confirmed this association, identifying a block containing the rs4986790 allele (A-C, OR=3.11). COPD-TS exhibited elevated IL-6, IL-4, and IL-5 levels compared to smokers without COPD (SWOC), while COPD-BBS displayed higher IFN-γ, IL-6, and IL-10 levels. The AA carriers in the COPD-TS group had elevated IL-4, IL-5, and IFN-γ compared to carriers of AG or GG. Conclusions: The rs4986790 common allele and the A-C haplotype (rs4986790-rs4986791) were associated with a higher COPD risk in smokers; COPD patients carrying the AA genotype showed increased pro-inflammatory cytokines.